Children and young people's experiences and perceptions of self-management of type 1 diabetes: A qualitative meta-synthesis. Issue 2 (September 2019) - Tuohy, Ella; Rawdon, Caroline; Gallagher, Pamela; Glacken, Michele; Murphy, Nuala; Swallow, Veronica; Lambert, Veronica
The aim of this review was to conduct a meta-synthesis of the experiences and perceptions of self-management of type 1 diabetes of children and young people living with type 1 diabetes (CYPDs). Six databases were systematically searched for studies with qualitative findings relevant to CYPDs' (aged 8–18 years) experiences of self-management. A thematic synthesis approach was used to combine articles and identify analytical themes. Forty articles met the inclusion criteria. Two analytical themes important to CYPDs' experiences and perceptions of self-management were identified: (1) negotiating independence and (2) feeling in control. The synthesis contributes to knowledge on contextual factors underpinning self-management and what facilitates or impedes transition towards autonomous self-management for CYPDs.